The Optimization of Local Government Officials Succession Plan in Indonesia through Talent Management on Islamic Perspective - Ghofur Ahmad; Ahmad subagyo (Jurnal Hikmatuna, 2019)
This article describes the optimization of succession planning of the high leadership position in Government Agencies through the talent pool mechanism, that under the Law, the high leadership appointment can be conducted without through the open selection mechanism as long as the organization has been run a merit system. One requirement of this system is Succession Planning that obtained from The Talent Management. Targets used in this study are 30 respondents of the high leadership position candidates (equivalent to echelon III) in provincial and district/ city government. The method used is an action research method by the assessment center of potential and competence with the qualitative approach. The results showed that from 30 administrative officers who trained projection mapping and competence mapping program, approximately 43.33% of officers in the rising star quadrant, that is fully prepared area to projected as officers at the Pratama high leadership, then about 50% go into the quadrant 2 that is promotable area with some development on adjusted aspects.